Role of ferroptosis in atrial fibrillation: a review - Fan, Shaowei; Hu, Yuanhui; Shi, Jingjing (Frontiers in Pharmacology, 2025)
Cardiovascular disease remains the leading cause of mortality, with atrial fibrillation emerging as one of the most common conditions encountered in clinical practice. However, its underlying mechanisms remain poorly understood, prompting ongoing research. Ferroptosis, a recently discovered form of regulated cell death characterized by lipid peroxidation and disrupted cellular redox balance leading to cell death due to iron overload, has attracted significant attention. Since its identification, ferroptosis has been extensively studied in various contexts, including cancer, stroke, myocardial ischemia/reperfusion injury, and heart failure. Growing evidence suggests that ferroptosis may also play a critical role in the onset and progression of atrial fibrillation, though research in this area is still limited. This article provides a concise overview of the potential mechanisms by which ferroptosis may contribute to the pathogenesis of atrial fibrillation.